Challenges of implementing digital technologies in international enterprises - Zhang, Kuan (Management and Entrepreneurship: Trends of Development, 2024)
This study examines the major challenges multinational companies face when implementing digital technologies in various markets and proposes strategies to mitigate these obstacles. As digital technologies like IoT, AI, and blockchain become increasingly vital for maintaining competitiveness and operational efficiency, multinational enterprises (MNEs) must integrate them into their global operations. However, this process is fraught with challenges, particularly in areas such as technological infrastructure, regulatory compliance, talent shortages, and cultural differences. A key obstacle is the varying levels of technological infrastructure across regions, with some markets lacking the necessary resources for seamless digital adoption. Regulatory compliance further complicates the process, as companies must navigate differing data protection laws, industry standards, and requirements for cross-border data flows. Additionally, talent shortages, particularly in emerging markets, hinder the implementation of these advanced technologies due to a lack of skilled personnel. Cultural differences also influence how employees interact with and adopt new digital systems, potentially slowing down the integration process. To overcome these challenges, MNEs need to adopt localized strategies, such as developing lightweight software tailored to regional infrastructure, enhancing training programs to build local expertise, and ensuring adherence to regional data regulations. By implementing these solutions, multinational companies can effectively manage the complexities of global digital technology adoption and maintain their competitiveness. JEL Classification: F5, F6, O3